ANALISIS EFISENSI PENGGUNAAN PANEL SURYA UNTUK PENERANGAN JALAN DAN CCTV KEAMANAN LINGKUNGAN - Ahmad Muflih Adzhar; Dan Mugisidi (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2025)
Reliance on PLN electricity for street lighting (PJU) and security CCTV requires high operational costs and is vulnerable to outages. Solar panels (PV) are a sustainable, efficient, and environmentally friendly renewable energy solution to improve security while reducing carbon emissions. This study aims to analyze the technical efficiency and economic feasibility of an integrated solar panel system to power street lighting and security CCTV in a neighborhood. The methods used were literature review and system calculation analysis (mathematical simulation). The calculations involved determining the daily power requirements of the street lighting and CCTV, the required solar panel capacity (Watt-peak), and battery capacity. Panel power efficiency was investigated based on irradiation intensity and tilt angle. The analysis results indicate that the PV system is highly effective and has potential. System efficiency can be significantly increased (15-20%) by implementing automatic/IoT controls. Although the initial installation costs tend to be higher, in the long term, this system is significantly more economical than conventional systems, providing sustainability and energy independence benefits